Respuesta :

Answer:

(-6, 36)

Step-by-step explanation:

The standard form: ax^2 + bx + c

In this case:

a is 1

b is 12

c is 0

Calculate -b / 2a. This is the x-coordinate of the vertex.

To find the y-coordinate of the vertex, simply plug the value of -b / 2a into the equation for x and solve for y. This is the y-coordinate of the vertex.

-12 / ( 2 x 1 )

-12 / 2

-6

You log -6 in the function

f(x) = x^2 + 12x

f(-6) = (-6)^2 + 12(-6)

      = 36 +  (-72)

      = 36 - 72

      = 36

I hope this

Answer: A (-6, -36)

Step-by-step explanation: